the Empowerment and Independence of Self-Help Farmers in Oil Palm Rejuvenation in Riau Province - miranti mandasari; rosnita; syaiful hadi (UNIVERSITAS LANCANG KUNING, 2022)
This research aims to 1) Study palm oil farming conducted by self-help farmers with reference to the application of ISPO, 2) Review the level of empowerment and independence of self-help palm oil farmers in Riau Province, 3) Analyze factors that have an influence in the level of empowerment and independence of self-help palm oil farmers in Riau Province. The study was conducted in 27 villages in 9 sub-districts of 3 districts in 2019 in Riau Province. The number of samples who became respondents was as many as 270 respondents of self-help palm oil farmers. Analytical methods are used descriptive analysis and Structural Equation Models (SEM). Research shows that the power and independence of self-help farmers is still low in the framework of oil palm rejuvenation in Riau Province according to ISPO criteria. The most dominant indicator affecting the power of farmers and farming groups is the perception of farmers' abilities and followed by agricultural business sapta. The most dominant indicator in influencing the independence of farmers and peasant groups is decision making in the selection of commodity types and marketing system decision making.